DETERMINING THE OPTIMUM TEMPERATURE FOR GROWTH, FEED EFFICIENCY AND SURVIVAL OF DOMESTICATED INDONESIAN MAHSEER, Tor soro LARVAE - Jojo Subagja; Emir Ma’arif Imanudin; Kurniawan Kurniawan; Agoes Soeprijanto; Yunita Maemunah (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Temperature plays a pivotal role in the success of larvae production. Evaluation of the effects of different temperatures on growth, feed efficiency, and survival of domesticated Indonesian mahseer (Tor soro) larvae was carried out to determine an optimum rearing temperature. Five different temperature settings of 22°C, 24°C, 26°C, 28°C, and 30°C were used as the treatments arranged in triplicates, in indoor closed recirculating systems. The larvae were stocked in a rectangular glass tank with a stocking density of 150 larvae per tank and fed with a commercial feed (30% protein content) three times a day, about 10% per body weight over 61 days of observation. Measured parameters included the specific growth rate of total weight (SGRTW) and length (SGRTL), feed efficiency (FE), and survival rate (SR). The result showed that the treatments of different temperatures significantly affected the growth performance and feed efficiency of the larvae. The growth performance and feed efficiency of mahseer larva were much better at rearing temperature from 24°C to 28°C compared with those at 22°C and 30°C. There were no significant differences in SR in different temperatures tested. The SR was found to range from 86.44% to 100% in all treatments. Maintaining temperature ranging from 24°C to 28°C is the best rearing condition to achieve the optimum growth and feed efficiency of mahseer during the larval rearing period. The findings from this research could be set as a standard technique in larval rearing of Indonesian mahseer (Tor soro).